2013
DOI: 10.1504/ijaacs.2013.050689
|View full text |Cite
|
Sign up to set email alerts
|

Designing a passive brain computer interface using real time classification of functional near-infrared spectroscopy

Abstract: Passive brain-computer interfaces consider brain activity as an additional source of information, to augment and adapt the interface instead of controlling it. We have developed a software system that allows for real time brain signal analysis and machine learning classification of affective and workload states measured with functional near-infrared spectroscopy (fNIRS) called the online fNIRS analysis and classification (OFAC). Our system reproduces successful offline procedures, adapting them for real-time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Most previous work was either done in a simulator or with a small number of participants. In addition, the methods we described would apply to classifying workload in other contexts, such as game user experience evaluation or passive, adaptive user interfaces (similar to passive BCI work [1,9,35,44]), and our sample size is larger than most papers in those areas. This has implications for broader applications for real-time cognitive load assessment and evaluating user interface technology in the wild, beyond driver user interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Most previous work was either done in a simulator or with a small number of participants. In addition, the methods we described would apply to classifying workload in other contexts, such as game user experience evaluation or passive, adaptive user interfaces (similar to passive BCI work [1,9,35,44]), and our sample size is larger than most papers in those areas. This has implications for broader applications for real-time cognitive load assessment and evaluating user interface technology in the wild, beyond driver user interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…It is one of the essential techniques in text classification [3,41,52,71] and speech recognition [65], and has been employed in recent years in brain-computer interfaces [29,53] and other artificial intelligence applications. Data observed and collected from many environments are sequential in nature which explains the importance of sequence classification and the vast spread of its applications.…”
Section: Sequence Classificationmentioning
confidence: 99%
“…Girouard et. al built an application which altered music based on task predictions from an fNIRS processing algorithm [17]. Solovey et al's Brainput system adapted in real-time to a scenario where an interactive human-robot system changed its state of autonomy based on whether it detected a particular state of multitasking [46] and Peck et al demonstrated a passive adaptive movie recommendation system [37].…”
Section: Brain-computer Interfacesmentioning
confidence: 99%